Ichthyofaunal community structures in different types of Eastern Cape estuaries - Vorwerk, Paul D (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2001)
This investigation had three major objectives; firstly to document the estuarine fishes from several poorly studied Eastern Cape estuaries, secondly, to identify similarities and differences in the fish communities from permanently open and intermittently open estuaries, and thirdly, to establish which physico-chemical or environmental variables are responsible for the structuring of these communities. The study area incorporated 10 estuaries along a 70 km long stretch of the Eastern Cape coastline between the towns of Seafield (33° 32' 42" S, 27° 03' 05" E) in the south-east and Hamburg (33° 16' 45" S, 27° 29' 50" E) in the north-west. The systems investigated included two permanently open estuaries and eight intermittently open systems of varying sizes. Overall fish abundance and species richness in the study area revealed no significant seasonal variation. A contrast between open and closed estuaries was evident in the dominance of species from different estuarine dependence categories. Open estuaries comprised mainly category Ib, lla and IIb species, with a high proportion of category IV species. Closed estuaries were dominated by category IIa species, with few category IV species represented. Clear longitudinal trends in relative abundance were demonstrated for individual species. Margalefs species richness index for seine net catches, and a combination of the seine and gill net data, were significantly correlated with catchment size, mean annual runoff, estuarine area and linear length. Fish assemblages in the permanently open and intermittently open estuaries were significantly different (p<0.001) when analysed on a community and density basis. Similarly, the communities in large and small intermittently open estuaries differed significantly on a community (p=0.01) and density basis (p<0.001). These differences where caused by changes in abundance of the dominant estuarine resident and marine migrant species. The environmental variable that was dominant in accounting for these differences was the estuary mouth status. Estuarine resident species had smaller overall body lengths when compared with the marine migrant species. In addition, the estuarine resident species had smaller modal size classes in the closed estuaries when compared with the open estuaries. These differences may be linked to the foraging strategies of the species, as well as food availability and different levels of predation in the different estuary types. The marine migrant species did not show any trends in this respect although the closed systems had the largest individuals for all four dominant marine species. This finding may be linked to the inability of these species to breed in closed estuaries, thus channelling reproductive energy resources into somatic growth. In addition, prolonged periods of mouth closure prevent the emigration of large individuals back to the sea. Otter trawling was conducted in fiye estuaries and captured mostly demersal species. The otter trawl data confirmed the seine net community analysis, with significantly different communities identified in the permanently open and intermittently open estuaries (p=0.02), as well as in the small and large intermittently open estuaries (p=0.03). The environmental variables responsible for these community differences were mouth status and variables associated with estuarine size. The identification of estuary mouth status by this study as the most influential environmental factor is compounded by this "ariable affecting or being indicative of numerous other physico-chemical features. The large differences in the fish communities in different estuary types indicate the importance of each estuary type to various species. This should be taken into account before allowing any form of commercial fishing in these important nursery areas.
Keywords: Estuarine fishes -- South Africa -- Eastern Cape; Estuarine fishes -- South Africa